Is Word Order Responsive to Morphology? Disentangling Cause and Effect in Morphosyntactic Change in Five Western European Languages - Julie Nijs; Freek Van de Velde; Hubert Cuyckens (Entropy)
This study examines the relationship between morphological complexity and word order rigidity, addressing a gap in the literature regarding causality in linguistic changes. While prior research suggests that the loss of inflectional morphology correlates with the adoption of fixed word order, this study shifts the focus from correlation to causation. By employing Kolmogorov complexity as a measure of linguistic complexity alongside Granger Causality to examine causal relationships, we analyzed data from Germanic and Romance languages over time. Our findings indicate that changes in morphological complexity are statistically more likely to cause shifts in word order rigidity than vice versa. The causal asymmetry is robustly borne out in Dutch and German, though waveringly in English, as well as in French and Italian. Nowhere, however, is the asymmetry reversed. Together, these results can be interpreted as supporting the idea that a decline in morphological complexity causally precedes a rise in syntactic complexity, though further investigation into the underlying factors contributing to the differing trends across languages is needed.